Posttransplant cyclophosphamide‐based anti–graft‐vs‐host disease prophylaxis in patients with acute lymphoblastic leukemia treated in complete remission with allogeneic hematopoietic cell transplantation from human leukocyte antigen‐mismatched unrelated donors versus haploidentical donors: A study on behalf of the ALWP of the EBMT. Issue 22 (15th September 2022) - Nagler, Arnon; Labopin, Myriam; Arat, Mutlu; Reményi, Péter; Koc, Yener; Blaise, Didier; Angelucci, Emanuele; Vydra, Jan; Kulagin, Aleksandr; Socié, Gerard; Rovira, Montserrat; Sica, Simona; et al.
Abstract : Background: Both mismatched unrelated donor (MMUD) and haploidentical (haplo) transplantation are valid options in patients with high‐risk acute lymphoblastic leukemia (ALL) lacking a matched donor. Methods: The study compared the outcomes of adult patients with ALL in complete remission (CR) who underwent 9/10 MMUD versus haplo transplantation with posttransplant cyclophosphamide (PTCy) as graft‐vs‐host disease (GVHD) prophylaxis in 2010–2020. Results: The study included 781 patients (MMUD, 103; haplo, 678). The median age was 40 (19–73) and 38 (18–75) years, respectively ( p  = .51). The most frequent immunosuppression agents added to PTCy were mycophenolate mofetil (MMF)/cyclosporine A and MMF/tacrolimus. In vivo T‐cell depletion (anti‐thymocyte globulin) was administered to 21% and 8% of the transplants, respectively ( p  < .0001). Neutrophil (absolute neutrophil count >0.5 × 10 9 /L) recovery was achieved in 97.1% versus 96.7% versus ( p  = 1) in MMUD and haplo, respectively. Nonrelapse mortality and relapse incidence were not significantly different between MMUD and haplo, hazard ratio (HR) = 1.45 (95% confidence interval [CI], 0.81–2.62; p  = .21) and HR = 0.81 (95% CI, 0.52–1.28, p  = .38), respectively. HRs for leukemia‐free survival, overall survival, and GVHD‐free, relapse‐free survival were respectively, HR = 1.05 (95% CI, 0.73–1.50, p  = .8), HR = 1.17 (95% CI, 0.77–1.76, p  = .46), and HR = 1.07 (95% CI, 0.78–1.46, p  = .7) for haplo compared to MMUD. Acute (a)GVHD grade 2–4 was significantly higher with haplo, HR = 1.73 (95% CI, 1.08–2.76, p  = .023), whereas aGVHD grade 3–4 and chronic GVHD did not differ significantly between the two transplant groups. Conclusion: Outcomes of MMUD and haplo transplants with PTCy‐based GVHD prophylaxis for ALL patients in CR are similar, apart from a higher incidence of aGVHD with haplo transplants. Abstract : The outcomes of mismatch unrelated and haploidentical transplants in patients with acute lymphocytic leukemia (ALL) in complete remission are similar. The donor pool for patients with ALL who are in need of allogeneic transplantation and do not have a human leukocyte antigen‐compatible donor is, therefore, enlarged.